Do Hospital Boards matter for better, safer, patient care?. (March 2017) - Mannion, R.; Davies, H.T.O.; Jacobs, R.; Kasteridis, P.; Millar, R.; Freeman, T.
Abstract: Manifest failings in healthcare quality and safety in many countries have focused attention on the role of hospital Boards. While a growing literature has drawn attention to the potential impacts of Board composition and Board processes, little work has yet been carried out to examine the influence of Board competencies. In this work, we first validate the structure of an established 'Board competencies' self-assessment instrument in the English NHS (the Board Self-Assessment Questionnaire, or BSAQ). This tool is then used to explore in English acute hospitals the relationships between (a) Board competencies and staff perceptions about how well their organisation deals with quality and safety issues; and (b) Board competencies and a raft of patient safety and quality measures at organisation level. National survey data from 95 hospitals (334 Board members) confirmed the factor structure of the BSAQ, validating it for use in the English NHS. Moreover, better Board competencies were correlated in consistent ways with beneficial staff attitudes to the reporting and handling of quality and safety issues (using routinely collected data from the NHS National Staff Survey). However, relationships between Board competencies and aggregate outcomes for a variety of quality and safety measures showed largely inconsistent and non-significant relationships. Overall, these data suggest that Boards may be able to impact on important staff perceptions. Further work is required to unpack the impact of Board attributes on organisational aggregate outcomes. Highlights: The Board Self assessment Questionnaire was validated for use in the English NHS. Board competencies were correlated with beneficial staff attitudes to the reporting and handling of patient safety issues. Board competencies were not found to be related to a range of patient safety outcomes.